Law, Contestation, and Power in the Global Political Economy: An Introduction. - Edward S. Cohen; A. Claire Cutler (Oñati Socio-Legal Series)
The papers included in this collection are part of concerted project to develop a political economy of law in the contemporary global system. Over the past two decades, scholars have noted the expanding role of law, legal institutions, and legal agents that have been part of the process of “globalization,” and have employed a number of frameworks to make sense of this process of legalization. A central theme of our project is that none of these frameworks has provided an adequate political economic analysis of the creation, diffusion, and use of law, and we present an alternative approach to advance the understanding of the turn to law across the many dimensions and sectors of the global system. The papers advance the analysis behind this approach and explore the various ways in which law matters in a variety of areas, including global finance, corporate governance, copyright, diplomacy, and the provision of security. Their goal is to advance our understanding of how law intersects with the mobilization of power in the construction of the contemporary political economy.